Literature Review Strategi Manajemen Stres Mahasiswa S1 Manajemen Universitas Muhammadiyah Kalimantan Timur di Era Akademik Modern - Hesty Eka Ardianty; Rachma Octavianti; Herlina .; Hera Erwanda; Rahmah Dani; Nagiyatus Sholihah; Dharma Desti; Astrid Suci Avilla; Yasinta Eka Nur Utami; Azka Murwandi Kholid; Septilia Nasfah; Kartika Setia Purdani; M. Bachtiar Safrudin (CV. ITTC INDONESIA, 2026)
Management students at the Universitas Muhammadiyah Kalimantan Timur face complex academic pressures in the modern era, which risk triggering stress and decreasing productivity. This study aims to identify stress triggers and formulate effective stress management strategies through a literature review method of 15 national and international scientific journals published in 2022-2025. The results of the study show that piled-up assignments, short deadlines, and academic grade pressure are the main stressors that manifest in physical symptoms such as headaches and psychological symptoms in the form of anxiety and overthinking. The impact of such stress includes decreased concentration, burnout, and disrupted social relationships. The conclusion of this study emphasizes that the implementation of structured time management strategies, social support, and simple relaxation techniques such as deep breathing, soothing music, and gadget restriction are proven effective as adaptive coping mechanisms for students in maintaining mental well-being and academic success.